2009
DOI: 10.3844/ajbbsp.2009.63.74
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Indian Cotton (Gossypium hirsutum) Harboring Rice Chitinase Gene (Chi II) Confers Resistance to Two Fungal Pathogens

Abstract: Problem statement: The present investigation described a simple and reproducible protocol for transgenic cotton regeneration and characterization of chitinase (Chi II) gene expression against two different fungal pathogens in cotton. Approach: Transgenic cotton (Gossypium hirsutum cv. SVPR2) plants were produced by pCambia-bar-Chi II (13.8 kb) under the control of the CaMV 35S promoter, harbored in the strain LBA 4404 Agrobacterium tumefaciens by using shoot tip explants. Results: Finally, from the 10 experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Among these, it is one of the diagnostic tool for transformed cells detection. Likewise, in the present investigations the presence of rice chitinase gene (chiII) in transformed plants was confirmed by amplifying 584 bp and 237 bp size fragments through PCR as previously reported by Ganeshan et al, 2009;Sharma et al, 2012 who also used the same construct in case of cotton and apple rootstock 'MM106' respectively.…”
Section: Discussionsupporting
confidence: 51%
“…Among these, it is one of the diagnostic tool for transformed cells detection. Likewise, in the present investigations the presence of rice chitinase gene (chiII) in transformed plants was confirmed by amplifying 584 bp and 237 bp size fragments through PCR as previously reported by Ganeshan et al, 2009;Sharma et al, 2012 who also used the same construct in case of cotton and apple rootstock 'MM106' respectively.…”
Section: Discussionsupporting
confidence: 51%
“…In a very first demonstration, the expression of bean chitinase in transgenic tobacco confers protection against Rhizoctonia solani (Brogue et al 1991). Furthermore, in a recent study, Shin et al (2008) has demonstrated resistance to Fusarium graminearum in transgenic wheat that expresses barley chitinase II, while the protection against two fungal pathogens, Fusarium oxysporum and Acarosporina microspora, was observed in transgenic Indian cotton that expresses the rice chitinases ChiII gene (Ganesan et al 2009). However, there are only a few reports on the successful engineering of tomato resistance against Fusarium wilt using transgenic methods.…”
Section: Discussionmentioning
confidence: 94%
“…Different structure and roles of plant chitinases had been found during plant evolution. Till now, several genes encoding chitinases have been cloned from many plants (Fortunato et al, 2007;Baranski et al, 2008;Ganesan et al, 2009;Liu et al, 2010;Taira et al, 2011). Several plant chitinases are constitutive, developmentally regulated and tissue-or organ-specific.…”
Section: Introductionmentioning
confidence: 99%